Педагогічні умови формування креативного потенціалу студентів у процесі вивчення іноземної мови майбутніх вчителів іноземних мов - Оніщук, Ірина (My University, 2018)
Креативність відіграє важливу роль у процесі іншомовної освіти. Важливим завданням викладача є зацікавити студентів та створити на занятті творчу атмосферу, у якій студентам буде цікаво пізнавати нове та відкривати для себе нові сфери можливостей застосування іноземної мови. Intensification of the process of exchange of achievements in the spheres of politic, economy, culture and diverse spiritual values leads to a steady increase in the requirements for in-depth study of a foreign language. The training of highly skilled foreign language specialists requires the training of highly skilled pedagogical staff for higher education institutions in the country with creative thinking. The level of foreign language mastery by graduates of the higher educational establishment is not in line with international standards. This greatly complicates the process of familiarizing future specialists with advanced foreign technology, as well as with foreign models of organization of economy and culture. Ability to communicate with a help of foreign language is a necessity of a future specialist. However, despite the importance of knowledge of a foreign language, while studying there are some difficulties, including the problem of communication. In order to avoid such situations, in the learning process, it is necessary to use a creative approach that promotes communication skills among students. The purpose of teaching a foreign language should be to promote a deeper understanding of other cultures, because the language should be considered not as simple language exercises, but as an opportunity to know the way of life, literature and the customs of others. Formation of creativity of students in the course of studying a foreign language is inextricably linked with the process of improving the professional competence of the teacher, since the creative approach in teaching develops the professional abilities of both the teacher and students who learn the language. To identify the role of a creative approach to teaching, the meaning of the term «creativity» should be considered. So, in our understanding, creativity is the activity of the individual, focused on creating a new, original product in the field of science, art, technology, production and organization. It is always a focus on a new, unexplored task solution, giving new opportunities for development.
Keywords: креативність; іншомовна освіта; освітній процес; особистісний підхід; creativity; foreign language education; educational process; personal approach